Control of Heavy Metal Pollution in Degraded Rural Areas (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents the issue of heavy metals in the different types of degraded territory in rural areas. For the test was chosen three different degraded territory: the former petrol station, the former farm mechanical workshop, the former farm cattle storage. All of three objects during operation were subjected to intensive polluting impact. They are included in the contaminated and potentially contaminated sites register. High concentrations of heavy metals in the soil of degraded territory is a factor that affects the planning for regeneration. Revitalization of contaminated sites and further use of them is possible only after the remediation works.